Effect of Acute Stroke Care Regionalization on Intravenous Alteplase Use in Two Urban Counties. (3rd July 2020) - Govindarajan, Prasanthi; Shiboski, Stephen; Grimes, Barbara; Cook, Lawrence J.; Ghilarducci, David; Meng, Tong; Trickey, Amber W.
Abstract : Importance: Intravenous alteplase is an effective treatment for acute ischemic stroke and is significantly underutilized. It is known that stroke centers with accreditation are more likely to provide intravenous alteplase treatment, and therefore, policies that increase the number of certified stroke centers and the number of acute ischemic stroke patients routed to these centers may be beneficial. Objective: To determine whether increasing access to primary stroke centers (regionalization) led to an increase in intravenous alteplase use in acute ischemic stroke patients. Design: An observational, longitudinal study to examine treatment trends with log-link binomial regression modeling to compare pre-post policy implementation changes in the proportions of patients treated with intravenous alteplase in two counties. Setting: Two urban counties, Santa Clara and San Mateo, in the western region of US that regionalized acute stroke care between 2005 and 2010. Participants: Patients with primary or secondary diagnosis of stroke were identified from the statewide patient discharge database by International Classification of Diseases (ICD-9) codes. We linked ambulance and hospital data to create complete patient care records. Main outcomes and measures: Stroke treatment, defined as a documented primary procedure code for intravenous alteplase administration (ICD-9: 99.10). Results: In Santa Clara County, intravenous alteplase was administered to 35 patients (1.7%) in the pre-regionalization period and 240 patients (2.1%) in the post-regionalization period. In San Mateo County, intravenous alteplase was administered to 29 patients (1.3%) in the pre-policy period and 135 patients (3.2%) in the post-policy period. After regionalization of stroke care, intravenous alteplase increased two-fold in San Mateo County [adjusted RR 2.20, p  = 0.003, 95% CI (1.31, 3.69)] but did not show any statistically significant change in Santa Clara County [adjusted RR 1.10, p  = 0.55, 95% CI (0.80, 1.51)]. In the post-regionalization phase, when compared with Santa Clara County, we found that San Mateo County had greater change in paramedic stroke detection, higher number of transports to primary stroke centers and more frequent use of intravenous alteplase at stroke centers. Conclusions: Our findings suggest that greater post-regionalization improvements in San Mateo County contributed to significantly better county-level thrombolysis use than Santa Clara County.